2020
DOI: 10.3389/fpsyt.2019.00955
|View full text |Cite
|
Sign up to set email alerts
|

Persisting Reductions in Cannabis, Opioid, and Stimulant Misuse After Naturalistic Psychedelic Use: An Online Survey

Abstract: Background: Observational data and preliminary studies suggest serotonin 2A agonist psychedelics may hold potential in treating a variety of substance use disorders (SUDs), including opioid use disorder (OUD). Aims: The study aim was to describe and analyze self-reported cases in which naturalistic psychedelic use was followed by cessation or reduction in other substance use. Methods: An anonymous online survey of individuals reporting cessation or reduction in cannabis, opioid, or stimulant use following psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 95 publications
(119 reference statements)
4
61
0
Order By: Relevance
“…Although ayahuasca has been shown to rapidly relieve depression symptoms in treatment-refractory depression in controlled clinical settings (Osório et al, 2015;Palhano-Fontes et al, 2019), the use of DMT and 5-MeO-DMT in naturalistic settings is receiving considerable attention given the rapid improvements elicited in several mental health domains accompanied by longlasting decreases in drug and alcohol use and abuse (Davis et al, 2019;Uthaug et al, 2019Uthaug et al, , 2020Garcia-Romeu et al, 2020). In vitro evidence supports the notion that 5-MeO-DMT might be beneficial for drug and alcohol addiction.…”
Section: Ongoing Clinical Trialsmentioning
confidence: 91%
See 2 more Smart Citations
“…Although ayahuasca has been shown to rapidly relieve depression symptoms in treatment-refractory depression in controlled clinical settings (Osório et al, 2015;Palhano-Fontes et al, 2019), the use of DMT and 5-MeO-DMT in naturalistic settings is receiving considerable attention given the rapid improvements elicited in several mental health domains accompanied by longlasting decreases in drug and alcohol use and abuse (Davis et al, 2019;Uthaug et al, 2019Uthaug et al, , 2020Garcia-Romeu et al, 2020). In vitro evidence supports the notion that 5-MeO-DMT might be beneficial for drug and alcohol addiction.…”
Section: Ongoing Clinical Trialsmentioning
confidence: 91%
“…Aside from the improvement in depression, anxiety, and compulsion domains discussed so far, the enhancement of several behavioral, social, and cognitive domains have been reported after psychedelic exposure. These include reduced psychological distress (Hendricks et al, 2015), decreased opioid dependence (Pisano et al, 2017;Argento et al, 2019;Garcia-Romeu et al, 2020), decreased criminal behavior (Hendricks et al, 2018), enhanced creative divergent thinking and problem-solving skills (Kuypers et al, 2016;Sweat et al, 2016), proenvironmental behavior via increased nature relatedness (Forstmann and Sagioglou, 2017), and a decreased incidence of extreme political views (Nour et al, 2017;Lyons and Carhart-Harris, 2018).…”
Section: Long-term Neurobiological and Psychological Effects Of Psychedelic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the wide range of mental health concerns for which psychedelic therapy has shown promise, it has been suggested that this treatment approach may target underlying transdiagnostic mechanisms (16)(17)(18)(19)(20)(21). Recent research has indicated that the intensity of "mystical-type" (4,6,7,9,22) or "peak" experiences engendered by psychedelics (23) is predictive of positive therapeutic outcomes; however, it remains unclear how (i.e., via what fundamental psychological and neurobiological mechanisms) psychedelic therapy brings about lasting therapeutic changes.…”
Section: Introductionmentioning
confidence: 99%
“…Mystical‐type and insight experiences as measured using validated questionnaires were found to be highly correlated with one another while only indirectly correlated with improved psychological well‐being. Regression analyses showed mystical‐type and insight experiences to be highly correlated with improved psychological flexibility and feelings of personal meaningfulness which in turn were highly correlated with improved psychological outlook (Davis, Barrett, & Griffiths, 2020; Garcia‐Romeu et al, 2019; Garcia‐Romeu et al, 2020). Therefore, these studies suggest that it is the improved psychological flexibility and personal meaningfulness associated with mystical‐type and insight experiences which enables depressed and anxious individuals and people with substance use disorders to reframe how they view their medical conditions, themselves, their lives and relationships with others (Belser et al, 2017; Davis et al, 2020; Garcia‐Romeu et al, 2019, 2020; Spiegel, 2016; Watts, Day, Krzanowski, Nutt, & Carhart‐Harris, 2017).…”
Section: Mechanistic Understandingmentioning
confidence: 99%